Enhancing Workers' Welfare through Participatory Occupational Health Policies in Riau’s Manufacturing Industry - Jasmaniar; Marniati (Help: Journal of Community Service, 2024)
Workers’ welfare is a crucial determinant of productivity and sustainability in the manufacturing industry. In Riau, challenges such as inadequate occupational health policies and lack of awareness about health standards have negatively impacted workers’ well-being. This study aims to enhance workers' welfare through the participatory implementation of occupational health policies using the Participatory Action Research (PAR) approach. This community-based participatory research was conducted in three manufacturing companies in Riau. The PAR approach involved four key phases: problem identification, collaborative planning, implementation of health-focused interventions, and evaluation. Data were collected through surveys, focus group discussions, and workplace observations, involving both workers and management. Quantitative data on welfare metrics were complemented by qualitative insights from stakeholder interviews. The implementation of occupational health policies significantly improved workers’ welfare indicators, including reduced workplace accidents (by 25%), increased job satisfaction scores (from 65% to 85%), and enhanced worker productivity (by 15%). Qualitative findings revealed heightened awareness and cooperation among workers and employers regarding health and safety standards. Stakeholders reported that the participatory approach fostered a sense of ownership and accountability. The results demonstrate that participatory strategies are effective in addressing workplace health challenges in the manufacturing sector. The PAR approach enabled the co-creation of practical solutions tailored to local needs, fostering long-term commitment from all stakeholders. This study highlights the importance of involving workers and management in policy development to achieve sustainable improvements in welfare.